Revisiting the euro's trade cost and welfare effects - Gabriel Felbermayr; Marina Steininger (Kiel Institute for the World Economy (IfW), 2019)
When, about twenty years ago, the Euro was created, one objective was to facilitate intra-European trade by reducing transaction costs. Has the Euro delivered? Using sectoral trade data from 1995 to 2014 and applying structural gravity modeling, we conduct an ex post evaluation of the European Monetary Union (EMU). In aggregate data, we find a significant average trade effect for goods of almost 8 percent, but a much smaller effect for services trade. Digging deeper, we detect substantial heterogeneity between sectors, as well as between and within country-pairs. Singling out Germany, and embedding the estimation results into a quantitative general equilibrium model of world trade, we find that EMU has increased real incomes in all EMU countries, albeit at different rates. E.g., incomes have increased by 0.3, 0.6, and 2.1 percent in Italy, Germany, and Luxembourg, respectively.
Keywords: F15; F17; N74; 330; Euro; Trade; General Equilibrium; Quantitative Trade Models; European Union